Massachusetts in the woman suffrage movement revolutionary reformers - Berenson, Barbara F. (History Press, 2018)
"Massachusetts was at the center of the national struggle for women's rights. Long before the Civil War, Lucy Stone and other Massachusetts abolitionists opposed women's exclusion from political life. They launched the organized movement at the first National Woman's Rights Convention, held in Worcester. After the war, state activists founded the Boston-based American Woman Suffrage Association and Woman's Journal to lead campaigns across the country. Their activities laid the foundation for the next generation of suffragists to triumph over tradition. Author Barbara Berenson gives these revolutionary reformers the attention they deserve in this compelling and engaging story"--book cover